2016
DOI: 10.2174/1872312810666160411144358
|View full text |Cite
|
Sign up to set email alerts
|

Rate-Determining and Rate-Limiting Steps in the Clearance and Excretion of a Potent and Selective p21-Activated Kinase Inhibitor: A Case Study of Rapid Hepatic Uptake and Slow Elimination in Rat

Abstract: Background: Significant under-prediction of in vivo clearance in rat was observed for a potent p21-activated kinase (PAK1) inhibitor, GNE1.Objective: Rate-determining (rapid uptake) and rate-limiting (slow excretion) steps in systemic clearance and elimination of GNE1, respectively, were evaluated to better understand the cause of the in vitro-in vivo (IVIV) disconnect.Methods: A series of in vivo, ex vivo, and in vitro experiments were carried out: 1) the role of organic cation transporters (Oct or Slc22a) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Work published in a poster supported the inference that 1-ABT does not interfere with transporters, as concentrations of 1-ABT up to 1 mM did not inhibit the MDR1, Bcrp1, and MRP2 transporters [ 76 ]. In another study, the in vivo clearance of GNE1, an inhibitor of the p21-activated kinase PAK1, was lower than predicted [ 77 ]. The use of transporter knockout rats with and without 1-ABT administration indicated that the clearance of this agent is determined by uptake transporters rather by metabolism.…”
Section: Specificity Of 1-abtmentioning
confidence: 99%
“…Work published in a poster supported the inference that 1-ABT does not interfere with transporters, as concentrations of 1-ABT up to 1 mM did not inhibit the MDR1, Bcrp1, and MRP2 transporters [ 76 ]. In another study, the in vivo clearance of GNE1, an inhibitor of the p21-activated kinase PAK1, was lower than predicted [ 77 ]. The use of transporter knockout rats with and without 1-ABT administration indicated that the clearance of this agent is determined by uptake transporters rather by metabolism.…”
Section: Specificity Of 1-abtmentioning
confidence: 99%
“…The reasons for IVIVE “disconnects” are often initially unknown and might be understood only later, following mechanistic absorption, distribution, metabolism, excretion (ADME) assays, and quantification of disposition and elimination pathways in vivo. Typical examples are compounds liable to active hepatic uptake, active renal elimination, , and/or extrahepatic metabolism. , Efforts to deconvolute disconnected IVIVE are lengthy and costly, likely opposing our ambition to replace, reduce, and refine use of animal studies. Can we do better?…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 illustrates differences in chemical space between Roche's discovery compounds tested in mouse PK and a set of marketed drugs compiled by Pfizer colleagues (panels A and B). 19 While overlaps exist, increases in median MW (477 vs 371 Da), lipophilicity (log P of 2.87 vs 2.0), and polarity (TPSA of 105 vs 89 Å 2 ) are notable for Roche's discovery dataset. Moreover, Roche's chemical space is continuously evolving with the recent decade bringing many more compounds with high MW (>500 Da) and polarity (TPSA > 140 Å 2 ) (Figure 1C,D).…”
Section: ■ Introductionmentioning
confidence: 99%
“…With recent advances in the drug transporter field, it has become apparent that uptake transporters at the sinusoidal membrane of hepatocytes play an important role in the hepatic clearance of drugs (Giacomini et al, 2010;Hillgren et al, 2013). Of note, organic anion transporting polypeptides (OATPs), organic anion transporter 2 (OAT2) and organic cation transporter 1 (OCT1) are shown to play an important role in the hepatic clearance of their substrate drugs, such as atorvastatin (Maeda et al, 2011), fluvastatin (Watanabe et al, 2010), cerivastatin (Shitara, 2011), repaglinide (Varma et al, 2013), bosentan (Sato et al, 2018) (OATP substrates), tolbutamide (OAT2 substrate) (Bi et al, 2018b), warfarin (OAT2 substrate) (Bi et al, 2018a) and GNE1 (OCT1 substrate) (Fan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%